Staphylinidae (Insecta: Coleoptera) of the Biologia Centrali-Americana: Current status of the names - Navarrete-Heredia, José Luis; Gómez-Rodríguez, Cecilia; Newton, Alfred F. (Zootaxa, 2006)
The Biologia Centrali-Americana (1879–1915), an obligate reference for the taxonomy of insects and other organisms from Mexico and Central America, is now available free on the web at http://www.sil.si.edu/digitalcollections/bca/. However, many included names are now out of date. We provide an updated list of all names of Staphylinidae (including Pselaphidae and Scaphidiidae) cited in the Biologia Centrali-Americana to use as a complement to that work. Of the 1610 staphylinid species-group names originally included, 929 remain as valid names without change, 581 have been previously transferred to other genera, 125 have been treated as junior synonyms, four treated as misidentifications of other names, and one (Cephaloplectus godmani Sharp, 1883) has been transferred to the family Ptiliidae. Our study also shows that 38 additional names should be transferred as new combinations to the genera Achenomorphus (from Aderocharis), Biocrypta and Homaeotarsus (from Ochthephilum), Neohypnus (from Xantholinus), and Platydracus (from Staphylinus and Amichorus), and seven species previously transferred to Medon should be returned to their original genus Scioporus as resurrected combinations.